Suplementasi Vitamin E dan Profil Lipid Penderita Dislipidemia: Studi pada Pegawai Rumah Sakit Profesor Dokter Margono Soekarjo Purwokerto - Diah Krisnansari; Martha Irene Kartasurya; M. Zen Rahfiludin (MEDIA MEDIKA INDONESIANA, 2011)
ABSTRACT Vitamin E supplementation and lipid profile in patients with dislipidemia Background: The prevalence of dislipidemia in Indonesia increase lately. Vitamin E has important role in cholesterol metabolism and protecting low density lipoprotein cholesterol against oxidation. This study was to investigate the effect of vitamin E supplementation on lipid profile.Method: The study was a randomised controlled clinical trial. Subjects were the employees of Professor Doctor Margono Soekarjo hospital aged 30-50 years who suffered from dislipidemic. The supplementation groups received 400 IU vitamin E and the control group received placebo once a day for 30 days. Lipid profile was examined using vitros system chemistry analyser 250 dan 350. Nutritional intake were gathered using food recall method and processed with nutrisurvey. Analyses were conducted using T-test, Mann Whitney, Wilcoxon and Chi square tests. Result: There were no differences in total (p=0.910), LDL (p=0.457) and HDL cholesterol levels (p=0.809) as well as trigliseride level (p=0.687) between the two groups before suplementation. There were differences in total (p=0.004) and LDL (p=0.002), there were no differences in HDL cholesterol level (p=0.332) and trigliseride level (p=0.940) between the two groups after supplementation. There were differences on the changes in total cholesterol (p=0.001) and LDL cholesterol (p=0.000) and no differences on the changes in HDL cholesterol level (p=0.197) as well as trigliserida level (p=0.438). There was no difference in nutritional intake between the two groups. Conclusion: That supplementation of vitamin E 400 IU once daily for 30 days improve lipid profile. Keywords: Dislipidemia, vitamin E, total cholesterol, LDL cholesterol, HDL cholesterol, trigliseride ABSTRAK Latar belakang: Angka kejadian dislipidemia di Indonesia semakin meningkat. Vitamin E merupakan antioksidan penting dalam metabolisme kolesterol, melindungi kolesterol LDL terhadap oksidasi dan meningkatkan kolesterol HDL. Penelitian ini bertujuan mengetahui pengaruh suplementasi vitamin E terhadap profil lipid penderita dislipidemia. Metode: Desain studi adalah acak buta ganda terkontrol dengan subyek 42 orang karyawan RS Profesor Dokter Margono Soekarjo penderita dislipidemia yang berusia 30-50 tahun, dibagi menjadi dua kelompok yaitu 22 orang memperoleh vitamin E 400 IU dan 20 orang memperoleh placebo sekali sehari selama 30 hari. Karakteristik subyek diperoleh melalui wawancara, berat badan dan tinggi badan diperoleh melalui pengukuran. Profil lipid diukur sebelum dan sesudah suplementasi dengan vitros system chemistry analyser 250 dan 350. Asupan gizi diperoleh melalui food recall dan dianalisis dengan program nutrisurvey. Data dianalisis dengan uji T, Mann Whitney, Wilcoxon dan Chi square. Hasil: Tidak ada perbedaan kolesterol total (p=0,910), kolesterol LDL (p=0,457), kolesterol HDL (p=0,809) dan trigliserida (p=0,687) antara kedua kelompok sebelum suplementasi. Ada perbedaan kolesterol total (p=0,004) dan kolesterol LDL (p=0,002), tidak ada perbedaan kolesterol HDL (p=0,332) dan trigliserida (p=0,940) antara kedua kelompok sesudah suplementasi. Ada perbedaan perubahan kolesterol total (p=0,001) dan kolesterol LDL (p=0,000), tidak ada perbedaan perubahan kolesterol HDL (p=0,197) dan trigliserida (p=0,438) antara kedua kelompok. Tidak ada perbedaan asupan gizi antara kedua kelompok. Simpulan: Suplementasi vitamin E 400 IU sekali sehari 30 hari dapat memperbaiki kolesterol total dan kolesterol LDL penderita.